The antimicrobial properties and chemical composition of leaf essential oils of indigenous Plectranthus ( Lamiaceae) species - Maistry, Kesheni (My University, 2003)
Species of the genus Plectranthus, a member of the mint family ( Lamiaceae ), have been used in alternative medicines in third world countries dating back to the early Chinese empire. Plectranthus species have been used in the past for coughs and colds (P. ambiguus) and as a mouth-wash for loose and bleeding teeth (P. laxiflorus). The crushed leaves of P. madagascariensis are used by Xhosa as an ointment for scabies P. hadiensis is used orally as a cough mixture. Eight species from the genus were chosen to study the essential oil composition and antimicrobial activity.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Medicine ( Pharmacotherapy)
Keywords: antimicrobial peptide; Chemistry; Plectranthus; Lamiaceae